Knowledge and Practice of Nursing Students Regarding Standard Precautions at a Tertiary Care Hospital - Naeem, Abid; Raza, Ahmad; Ali, Afsar (Indus Journal of Bioscience Research, 2025)
Background: Health professionals are increasingly at risk from contact with patients’ and other bodily fluids, which has been a major source of alarm for the wider public and leading figures in the field of medicine across the globe. Infections related to medical care pose a significant danger to those who work in the medical field. Objective: The objective of this study was to identify the knowledge and practice of nursing students regarding standard precautions at a tertiary care hospital. Methods: A descriptive cross sectional study was conducted among nursing students regarding standard precautions. Simple random sampling technique was used for data collection. Data was collected from a sample size of 121 participants by using pre-structured demographics, knowledge and practice based questionnaire from nursing students. Data was analyzed by using the SPSS 21 software for descriptive statistics. Results: The findings of this study revealed that majority of the participants 64.5% have an average knowledge (50% to 85%) regarding standard precautions, while 35.5% of the participants have an excellent knowledge (>85%). Similarly 56.2% of the participants have an average practice (50% to 85%), while only 37.2% of the participants have good practice (>85%), and 6.6% of the participants have poor practice (<50%) regarding standard precautions. Conclusion: The findings of this study suggest that more work needs to be done to ensure that students fully grasp the concepts of hospital acquired infections and strictly adhere to the standard precautions in the hospital settings. Standard precautions should be applied under strict surveillance and established norms with the aid of well-developed interventions that raise awareness and encourage the adoption of safe practices.